The Authority of the Professional Disciplinary Council and Its Implications for Legal Certainty for Medical and Health Personnel - Nefrisa Adlina Maaruf; Abdul Kholib; Beniharmoni Harefa (International Journal of Social Welfare and Family Law, 2025)
This study examines the changes in the authority of the Professional Disciplinary Council (Majelis Disiplin Profesi, MDP) under Law Number 17 of 2023 concerning Health and their implications for legal certainty for medical and health professionals. Although these changes are intended to improve the professional disciplinary system, they have resulted in the centralization of authority under the Ministry of Health, including the appointment of members, institutional formation, and the process of judicial review of MDP decisions. Furthermore, MDP recommendations can now serve as a basis for criminal investigations against medical and health personnel, which contradicts the original function of the MDP as an institution for enforcing ethics and professional discipline based on due process of ethics. This research employs a normative juridical method with a descriptive-analytical and case study approach, supported by expert interviews in health law. Theoretical frameworks used include the Theory of Legal Certainty, the Theory of Human Rights, and the Theory of Legal Protection. Findings indicate that the centralization of authority under the Ministry of Health has created a power imbalance in professional oversight. This has negative implications for legal protection, increasing the risk of conflict of interest, abuse of authority, and weakening legal certainty for medical and health professionals. Therefore, it is necessary to revise Law No. 17 of 2023 and Government Regulation No. 28 of 2024 to restore the independence of the MDP and ensure a proportional redistribution of authority within the health professional oversight system.